Assessing the knowledge and skills on emergency obstetric care among health providers: Implications for health systems strengthening in Nigeria - Okonofua, Friday (PLoS One, 2019)
OBJECTIVE: To assess the existing knowledge and skills relating to Emergency Obstetrics Care (EMOC) among health providers in eight referral maternity hospitals in Nigeria. STUDY DESIGN: A cross-sectional study of skilled health providers (doctors, nurses and midwives) working in the hospitals during the period. SETTING: Six general hospitals (4 in the south and 2 in the north), and two teaching hospitals (both in the Northern part) of the country. POPULATION: All skilled providers offering EMOC services in the hospitals during the study. METHODS: A pre-tested self-administered questionnaire was used to obtain information relating to socio-demographic characteristics, the respondents’ knowledge and skills in offering specific EMOC services (as compared to standard World Health Organization recommendations), and their confidence in transferring the skills to mid-level providers. Data were analyzed with univariate, bivariate, binary and multinomial logistic regression analyses. Main outcome measures: knowledge and skills in EMOC services by hospital and overall. RESULTS: A total of 341 health providers (148 doctors and 193 nurses/midwives) participated in the study. Averagely, the providers scored less than 46% in a composite EMOC knowledge score, with doctors scoring considerable higher than the nurses/midwives. Similarly, doctors scored higher than nurses/midwives in the self-reporting of confidence in carrying out specific EMOC functions. Health providers that scored higher in knowledge were significantly more likely to report confidence in performing specific EMOC functions as compared to those with lower scores. The self-reporting of confidence in transferring clinical skills was also higher in those with higher EMOC knowledge scores. CONCLUSION: The knowledge and reported skills on EMOC by health providers in referral facilities in Nigeria was lower than average. We conclude that the in-service training and re-training of health providers should be included in national policy and programs that address maternal mortality prevention in referral facilities in the country. TRIAL REGISTRATION: Nigeria Clinical Trials Registry 91540209.